1997
DOI: 10.1172/jci119272
|View full text |Cite
|
Sign up to set email alerts
|

Alpha-melanocyte-stimulating hormone protects against renal injury after ischemia in mice and rats.

Abstract: Reperfusion after ischemia induces cytokines, chemoattractant chemokines, adhesion molecules, and nitric oxide (NO). The resultant neutrophil adherence and NO potentiates renal injury. ␣ -Melanocyte-stimulating hormone ( ␣ -MSH) is a potent anti-inflammatory agent that inhibits neutrophil migration and production of neutrophil chemokines and NO. Since neutrophils and NO promote renal ischemic injury, we sought to determine if ␣ -MSH inhibits renal injury in a model of bilateral renal ischemia. ␣ -MSH significa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
193
2
6

Year Published

1998
1998
2014
2014

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 267 publications
(214 citation statements)
references
References 34 publications
13
193
2
6
Order By: Relevance
“…Previous animal studies clearly demonstrated that the treatment of AKI should be started well before the rise of Scr and very early after the insult (31)(32)(33)(34). Sensitive biologic markers of renal tubular injury are needed to detect early AKI because current AKI diagnosing and staging criteria are entirely based on an increase in Scr or decrease in urine output.…”
Section: Discussionmentioning
confidence: 99%
“…Previous animal studies clearly demonstrated that the treatment of AKI should be started well before the rise of Scr and very early after the insult (31)(32)(33)(34). Sensitive biologic markers of renal tubular injury are needed to detect early AKI because current AKI diagnosing and staging criteria are entirely based on an increase in Scr or decrease in urine output.…”
Section: Discussionmentioning
confidence: 99%
“…-MSH, an endogenous antiinflammatory cytokine, has been known to reduce cellular infiltrations in various inflammatory conditions such as rat model of arthritis and liver injury from septic shock (20)(21)(22)(23). -MSH also has been reported to have a beneficial effect in ischemia/ reperfusion injury through its inhibitory action on the mouse chemokine KC and ICAM-1 messages and on the induction of iNOS with a resultant decrease in peroxynitrate production (24). In our previous study, intraperitoneally administered -MSH was also effective in attenuating the severity of injury determined by biochemical and histological data.…”
Section: Discussionmentioning
confidence: 99%
“…et al reported a beneficial effect of -MSH in murine model of ischemic acute renal failure (ARF) through an inhibition of mouse chemokine KC and intercellular adhesion molecule-1 (ICAM-1) expression that mediates the adherence of neutrophils to endothelium and the subsequent neutrophil infiltration (24). In addition, we have observed that tubular cell apoptosis also significantly decreased in -MSH treated group in ischemic ARF rat model with concomitant decrease in Fas/FasL protein expression and suggested that the beneficial effects of -MSH might be partially related to its inhibitory action on Fas/FasL system and apoptosis (25).…”
Section: Introductionmentioning
confidence: 99%
“…Modulation of the inflammatory response has been shown to improve renal function after I/R. For instance, the anti-inflammatory agent, α-melanocyte stimulating hormone (α-MSH), protects the kidney against ischemic injury but also inhibits neutrophil chemotaxis (135). Similarly, infusion of a tumor necrosis factor (TNF)-α binding protein decreased neutrophil infiltration and preserved renal function, suggesting a deleterious role for the upregulation of TNF-α in renal I/R (136).…”
Section: Activation Of Inflammation and Endothelial-leukocyte Interacmentioning
confidence: 99%